The Role of Agricultural Credit in Reducing Rural-to-Urban Migration - Valiyeva, Asmar; Mammadli, Mehman (My University, 2026)
Urbanization can create jobs and stimulate economic activity; however, excessive migration from rural areas may threaten food security, strain city services and exacerbate inequalities among regions. This study investigates relation between better access to agricultural credit and urbanization, and tries to find answer if this relation can help to decrease migration from rural to urban areas. Panel data from 129 countries covering the period 1991-2023 were used to examine the relationship between access to agricultural credit and urbanization. Additionally, one-, two-, and three-year lagged specifications were also estimated to assess delayed effects of agricultural credit to urbanisation. Results indicated that there is no statistically significant effect of current use of agricultural credit on urbanization. However, the lagged estimates show increasingly negative and statistically significant impact. Findings from this research suggest that agricultural credit represents an effective tool for promoting rural development when assessed over an appropriately large time frame. Recommendations for policymakers include targeted delivery of agricultural credit to smallholders with a goal of creating viable rural livelihoods that reduce the incentive for individuals to migrate from rural to urban areas.
Keywords: agricultural credit; rural-to-urban migration; urbanization; rural development; panel data; fixed effects